2011
DOI: 10.1175/2010mwr3396.1
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Atmosphere–Wave–Ocean Modeling System: Simulation of the Intensity of an Idealized Tropical Cyclone

Abstract: A coupled atmosphere–wave–ocean modeling system (CAWOMS) based on the integration of atmosphere–wave, atmosphere–ocean, and wave–current interaction processes is developed. The component models consist of the Weather Research and Forecasting (WRF) model, the Simulating Waves Nearshore (SWAN) model, and the Princeton Ocean Model (POM). The coupling between the model components is implemented by using the Model Coupling Toolkit. The CAWOMS takes into account various wave-related effects, including wave state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 86 publications
5
93
0
Order By: Relevance
“…Thus, SWH differences up to 1.2 m occur over the areas of the maximum wind speed reduction (e.g., the area between the Balearic and Tyrrhenian seas). Similar results have been also observed by Doyle (2002), Janssen (2004), Liu et al (2011), andRenault et al (2012).…”
Section: System Configurationsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, SWH differences up to 1.2 m occur over the areas of the maximum wind speed reduction (e.g., the area between the Balearic and Tyrrhenian seas). Similar results have been also observed by Doyle (2002), Janssen (2004), Liu et al (2011), andRenault et al (2012).…”
Section: System Configurationsupporting
confidence: 90%
“…Generally, at shorter and even more at longer scales, reliable results can be obtained by considering the fluid layer surrounding Earth as a single system. This means to simulate the atmosphere and the ocean as a single fully coupled system and to construct multi-model, multi-scale integrated systems (Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Doyle (2002) found that including atmosphere-surface wave coupling for three simulated hurricanes produced negligible instantaneous maximum wind speeds (< 0.1 ms -1 average of three cases over four time periods) and led to a one meter smaller significant wave heights compared to the uncoupled simulations. However, idealized air-ocean-wave coupled model hurricane simulations by Liu et al (2011) indicated the atmospheresurface wave coupling increased the maximum wind speed by 8 ms -1 . In their idealized simulations, the TC intensity in the coupled atmosphere-ocean-wave model was generally reduced relative to the uncoupled simulation due to the larger ocean cooling underneath the TC.…”
Section: E Surface Wave Effects On the Upper-ocean Mixingmentioning
confidence: 98%
“…Zhao et al (2006) proposed an SSGF dependent on the windÁsea wave Reynolds number for droplets with radii of 30Á500 mm. To extend the SSGF to droplets with radii under 30 mm, we used the same method as Liu et al (2011. introduced the whitecap coverage function into the SSGF of Monahan (1986) and developed a windÁsea Reynolds number-dependent SSGF for droplets smaller than 20 mm.…”
Section: Improved Wind Stress Parameterisation From Comparing the Usmentioning
confidence: 99%